Evaluation of the performance of α-SiAlON tool when turning Ti-6Al-4V alloy without coolant - Souza, J. V C; Nono, M. C A; Mineiro, S. L.; Ribeiro, M. V. [UNESP]; Silva, O. M M (Trans Tech Publications, 2008)
Due to their high hardness and wear resistance, Si3N4 based ceramics are one of the most suitable cutting tool materials for machining cast iron, nickel alloys and hardened steels. However, their high degree of brittleness usually leads to inconsistent results and sudden catastrophic failures. This necessitates a process optimization when machining superalloys with Si3N4 based ceramic cutting tools. The tools are expected to withstand the heat and pressure developed when machining at higher cutting conditions because of their high hardness and melting point. This paper evaluates the performance of α-SiAlON tool in turning Ti-6Al-4V alloy at high cutting conditions, up to 250 m min-1, without coolant. Tool wear, failure modes and temperature were monitored to access the performance of the cutting tool. Test results showed that the performance of α-SiAl0N tool, in terms of tool life, at the cutting conditions investigated is relatively poor due probably to rapid notching and excessive chipping of the cutting edge. These facts are associated with adhesion and diffusion wear rate that tends to weaken the bond strength of the cutting tool.
Keywords: α-siaion; Machining; Si3n4; Ti-6al-4v; Turning; Bond strengths; Catastrophic failures; Cutting conditions; Cutting edges; Hardened steels; High hardnesses; Higher cutting conditions; Process optimizations; Sin; Test results; Ti-6al-4v alloys; Tool lives; Tool materials; Tool wears; Wear rates; Alloys; Aluminum; Cast iron; Ceramic cutting tools; Ceramic materials; Ceramic tools; Cerium alloys; Coolants; Failure analysis; Fracture mechanics; Hardness; Machine tools; Melting point; Metal working tools; Metallic compounds; Nickel alloys; Optimization; Powders; Silicon; Silicon alloys; Titanium alloys; Wear resistance; Cutting tools